Surgical treatment of severe thoracic kyphosis and neurological deficit in a patient with Gorham–Stout syndrome: A case report and literature review - Zhang, Hanwen; Han, Chaofan; Pang, Daming; Yong, Hai; Yang, Jincai; Yin, Peng; Zhou, Lijin (Frontiers in Surgery, 2022)
Abstract Background: Gorham–Stout syndrome is a rare disorder of unknown aetiology and variable clinical presentation that is characterised by a proliferation of lymphatic vessels and massive regional osteolysis. Spinal and visceral involvement increases the syndrome’s morbidity and mortality rates. Here, we report about a male patient with Gorham’s disease who developed local kyphosis and neurological disorders due to massive osteolysis. Case presentation: A 13-year-old male patient presented with progressive kyphosis and massive osteolysis of the thoracic vertebrae. Halo-pelvic traction and vertebral column resection osteotomy were performed to reconstruct the spine and prevent disease progression. The entire lesion was resected, and an artificial vertebra filled with allograft bone was used to achieve temporary stability. Although the patient presented with chylothorax following surgery, which required thoracic drainage, the patient did achieve a satisfying outcome. Conclusions: Limited by the number of GSS cases with spinal involvement and chylothorax manifestations, halo-pelvic distraction as a preoperative preparation and vertebral column resection osteotomy provide a novel avenue for managing this disease.